An investigation of wine quality testing using machine learning techniques - Sathishkumar Mani; Reshmy Avanavalappil Krishnankutty; Sabaria Swaminathan; Prasannavenkatesan Theerthagiri (IAES International Journal of Artificial Intelligence (IJ-AI), 2023)
Quality is the most determining factor for any product. Optimal care and best measures are to be taken in assessing the quality of any product. This work deals with determining the quality of wine using intelligence-based learning techniques. In order to estimate the quality of wine, several experiments are performed on wine datasets. The main purpose of our work is to study and discover an efficient machine learning (ML) model that could determine the quality of wine given some Physico-chemical features. This study establishes that selecting important features to evaluate rather than all of them can lead to improved forecasts. According to the results, this approach may provide people who are not wine experts a greater opportunity to choose a fine wine.